Atypical Kaposi Sarcoma of the Tongue in HIV Positive Tanzanian Female - Elichilia Shao; Flora Ruhangisa; Neema Minja; Kanankira Nnko; Denis Katundu; George Semango; Eva Mbwilo; Amos Mwasamwaja; Kajiru Kilonzo; Isaack Lyaruu (Case Reports in Infectious Diseases)
We report atypical case of Kaposi Sarcoma (KS) in a 32-year-old human immunodeficiency virus- (HIV-) infected female, involving only the tongue. Viral loads and CD4 T cells were measured and were 65,000 cps/mL and 10 cells/mL, respectively. This patient was newly diagnosed and had no history of antiretroviral therapy (ART), radiotherapy, or immunosuppressive drugs prior to this admission. Clinically, there were no dermatological features of KS lesions which are purple, red, or brown and which may be flat, raised (plaques), or bumpy (nodules) except for fungating and protruding enlarged tongue which was necrotic. Histologically, it was proven to be the most common type of KS “epidemic” or AIDS-related KS.